ASAJERE: Measuring the Meaning of the Return Ritual of Madura Hajj Pilgrimages from a Socio-Anthropological Perspective - Faiz Yasin; Hasyim Hasanah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Tradition and worship are inseparable from Muslims, as part of religious rites that are rich in meaning and individual experiences, one of which is the Hajj tradition. This study aims to describe and analyze the meaning of the Asajere tradition for the Madurese Muslim community. The research method used is a qualitative method, descriptive-interpretive. This study uses a socio-anthropological approach. The data sources for this study come from Hajj pilgrims and the Madurese community who still practice the Asajere tradition in Gajamsana Daya Village, Pasean District, Pamekasan Regency. The researcher also uses supporting data sources from religious leaders and the Madurese community. To ensure the validity of the data, the author uses source triangulation techniques. This study results in the finding that Asajere is a form of Hajj tradition carried out to welcome the return of Hajj pilgrims. Asajere has a very philosophical meaning, as an expression of gratitude as well as a socio-religious mechanism to strengthen the moral legitimacy and social status of Hajj pilgrims in society. This tradition embodies a strong social dynamic, encompassing social solidarity, symbolic social interaction, and cultural behavior management, reflecting the principles of culture-based Hajj management. Asajere serves as a form of cultural resistance to modernization by emphasizing the identity of adaptive, reflective, and contextual local wisdom.